Наукове забезпечення криміналістичних досліджень у третьому тисячолітті - Біленчук, П.; Ярмолюк, А.; Bilenchyk, P.; Yarmolyuk, A. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Сучасний етап розвитку світової цивілізації характеризується системними трансформаційними змінами, оскільки він обумовлений епохою глобалізації. Очевидно, що розвиток криміналістики в третьому тисячолітті обумовлений глобалізаційними процесами, а значить постійним прагненням науки до розширення обсягу досліджуємих об’єктів і можливості їх пізнання з допомогою сучасних ноозасобів, інтерактивних методів і грід- технологій. The current stage of development of the world civilization is characterized by systematic transformational changes because this stage is caused by the era of globalization. Clearly, the development of criminalistics in the third millennium is governed by the globalization processes, and hence, by permanent desire of science to expand the scope of objects under investigation and of possibilities of their perception by the means of modern nootools, interactive methods and grid technologies. Today criminalistics as a science has a prominent place in the perception of juridically significant facts, events and phenomena of the modern world. At the same time, historiography, source criticism, current stage and the ways of priority development of criminalistics are considered in the most perspective systematic approach through the prism of tridimensional world outlook: the first, to analyze the criminalistics as a science; the second, to determine criminalistics as a taught course (discipline); and the third, to highlight the criminalistics as a field of practice – expert, investigative, judicial, law enforcement and human rights.
Criminalistics in the Third Millenium: Education, Science, Practice
Keywords: криміналістика; наука; навчальна дисципліна; сфера практичної діяльності; грід- технології; criminalistics; a science; a taught course; a field of practice; grid-technologies